Asset maintenance maturity model: structured guide to maintenance process maturity. (2015) - Chemweno, Peter; Pintelon, Liliane; Horenbeek, Adriaan Van; Muchiri, Peter N.
In today's dynamic business environment, organisations are adapting asset management strategies as a means of gaining a competitive advantage. This is achieved through implementing effective maintenance program(s). However, implementing such program(s) is often not straightforward due to lack of a structured decision making framework. This article proposes a generic asset maintenance maturity model as a structured guide to maintenance process maturity. The proposed model aims at assessing the maintenance decision making capabilities within organisations. A weighted maintenance performance assessment score is proposed that facilitates performance measurement and benchmarking. Based on the weighted score, organisations are situated on a five-level maintenance maturity ladder. Moreover, the proposed approach incorporates risk assessment methodologies as a means of directing improvement actions towards maintenance maturity.